(untitled) (World Science, 2018)
The study was aimed to analyze theoretical material on the issues of idiomatic expressions and their translation, as well as to define and assess the importance of the translation of idiomatic expressions, which students can encounter in technical literature, into Ukrainian. The transformation of image of English idioms is a very difficult task because of their semantic richness, imagery, brevity and the brightness. On the one hand, English idioms are widely used in oral speech, artistic and political literature. On the other hand, English idioms are used in technical literature, though not so often. The choice of one or another type of translation depends on the features of idiomatic expressions that students must recognize and be able to transform their meaning, brightness and clarity.